Trends of energy input in some Nigerian palm oil mills (2011)
Energy audit was conducted using the energy accounting method in seven palm oil processing mills. The mills were stratified into small, medium and large categories based on the levels of mechanization and daily production capacity. The production process in three mill categories was divided into eight defined unit operations: bunch transportation, detachment and plucking, bunch sterilization, fruit digestion, pulp pressing, oil clarification, oil drying and oil packing. The energy (electricity, thermal and labour) consumption in each unit operation for processing 1,500 kg of fresh fruit bunch was evaluated. Results showed that the total energy intensity in the palm oil processing plants reduced with increase in levels of mechanization and daily production capacity from 344.98 MJ/tones in the small-scale plants to 252.43 MJ/tones in the large-scale plants. Percentage share of electrical energy in the total energy reduced from 96.73 to 95.06, while the thermal energy reduced from 3.27 to 1.84-%. The two identified energy intensive operations in palm oil processing are bunch transportation and fruit digestion, which accounted for over 90% of the total energy consumption in all the three mill categories. The use of fiber sludge as alternate source of energy for the boiler was recommended to reduce the cost of energy.